2016
DOI: 10.1097/dad.0000000000000453
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Lymphovascular Invasion Detected by Double Immunostaining for D2-40 and MITF1 in Primary Cutaneous Melanoma

Abstract: Background: Lymphovascular invasion (LVI) is associated with adverse outcomes in primary cutaneous melanoma (PCM). Detection of LVI by hematoxylin and eosin staining alone is 0%-6%, but targeting lymphovascular structures increases the detection rate.Objective: To examine the prognostic significance of LVI detected by immunostaining for D2-40 and microphthalmia-associated transcription factor 1 (MITF1) in PCM. Methods:The authors retrospectively analyzed 120 PCM samples.We compared the LVI detection rates of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Despite observing no association between LI within melanomas and SLN status, Rose et al showed a significant association between LI and disease‐free and overall survival in a multivariate analysis. In another study, there was no significant association with LI and clinical outcome, including lymph node metastasis, distant metastasis and survival . Xu et al found a significant association between LI and time to metastasis and melanoma‐specific death.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Despite observing no association between LI within melanomas and SLN status, Rose et al showed a significant association between LI and disease‐free and overall survival in a multivariate analysis. In another study, there was no significant association with LI and clinical outcome, including lymph node metastasis, distant metastasis and survival . Xu et al found a significant association between LI and time to metastasis and melanoma‐specific death.…”
Section: Discussionmentioning
confidence: 94%
“…In both univariate and multivariate analyses, Fohn et al showed that LI is the best predictor of SLN status when compared to mitotic rate, tumor thickness, presence of ulceration, patient age and patient gender. Feldmeyer et al also demonstrated that the detection of LI using dual immunohistochemistry is associated with SLN metastasis. In a study of "melanocytic tumors of uncertain malignant potential," Abraham et al showed that LI as detected by dual immunohistochemistry for D240 and S100 was associated with nodal metastasis and melanoma‐related death, suggesting that identifying LI in ambiguous melanocytic tumors may help predict tumors capable of metastasis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite these findings, a number of additional studies showed no association between the detection of lymphatic invasion in primary melanomas and survival (Table 1). 19,25,31 Egger et al 12 detected a significant difference in OS only by univariate analysis but showed that lymphatic invasion was associated with a worse OS in patients with regression. Interestingly, in a study of 116 melanomas with regression, Yun et al 40 found that patients with lymphatic invasion in areas of complete regression had a shorter time to first metastasis and melanoma-specific death than those who did not have lymphatic invasion, suggesting that the adverse prognostic effect of regression may be in part mediated by lymphatic invasion.…”
Section: Lymphatic Invasion and Survivalmentioning
confidence: 99%
“…Compared with H&E staining and/or immunohistochemical staining with a single vascular marker, double immunohistochemical staining with both a melanocytic and vascular marker (eg, S100+D2-40, MITF+D2-40, SOX-10+D2-40) has been reported to be more sensitive and specific for the detection of lymphovascular invasion in melanoma 54 55…”
Section: Immunohistochemical Aspects Of Melanoma Angiogenesismentioning
confidence: 99%